Multifunctional landscapes for dedicated bioenergy crops lead to low-carbon market-competitive biofuels. (November 2022) - Baral, Nawa Raj; Mishra, Shruti K.; George, Anthe; Gautam, Sagar; Mishra, Umakant; Scown, Corinne D.
Abstract: Switchgrass is a promising feedstock for cellulosic biorefineries, due to its ability to maintain comparatively high biomass yields across a wide range of soil and climatic conditions. However, there is an incomplete understanding of the economic and environmental tradeoffs associated with cultivating switchgrass on low-productivity land for conversion to biofuels. This study surveys prior literature and demonstrates a new integrated assessment framework, including agroecosystem, ecosystem services valuation, technoeconomic, and life-cycle assessment models, to quantify and contextualize the economic and environmental impacts of switchgrass cultivation on marginal land with downstream conversion to biofuels. Monetizing and incorporating the value of ecosystem services, such as improved water quality benefits from nitrate and sediment reductions, climate change mitigation benefits from CO2 emission reduction, and recreational and pollination benefits from increased biodiversity, the modeled multifunctional landscape reduces the ethanol production cost by 33.3–58.9 cents/l -gasoline-equivalent ($1.3–2.2/gge). Planting switchgrass in low productivity land improves soil health, resulting in the carbon footprint reduction credit of 12.8–20.2 gCO2e /MJ. For an improved switchgrass-to-ethanol conversion pathway with the maximum benefits from ecosystem services, the minimum ethanol selling price and carbon footprint of ethanol, respectively, could reach to 31 cents/l -gasoline-equivalent (47% reduction relative to average gasoline price) and 3 gCO2e /MJ (97% reduction relative to gasoline). This low carbon renewable ethanol leads to substantial State and/or Federal policy incentives (∼$1/l -gasoline-equivalent) providing a large benefit to biorefinery operators, farmers, and the public as a whole. Highlights: Ecosystem services benefits reduced the delivered switchgrass cost by $29–104/bdt. Switchgrass grown on marginal land increased carbon sequestration by 0.1–0.36 MgC/ha. Ecosystem services benefits reduced ethanol selling price reduced by 20–55%. Carbon footprint of ethanol reduced by 44–81% with ecosystem services benefits. Biorefinery operators could make profit of 28 cents/l -gasoline-equivalent.